Can one retell a Mozambican reform story through problem-driven iterative adaptation? - Matt Andrews (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Many public sector reforms in developing countries fail to make governments more functional. This is typically because reforms introduce new solutions that do not fit the contexts in which they are being placed. This situation reflects what has recently been called the 'capability trap' in development - which results in many interventions producing new forms that are not functional in states across the globe. The work on capability traps suggests that reforms can yield more functional influence in even the most complex states, however; but this is only if reformers adopt non-traditional approaches to doing reform. In particular, the work suggests that reforms will tend to be more contextually fitted if: (i) they are driven by problems that agents in the context care about; and (ii) they are introduced iteratively - through a stepwise process where ideas are tried and lessons are learned and used to adapt (or fit) ideas to context. The capability traps work embeds these ideas into an approach to doing reform called problem-driven iterative adaptation (PDIA). This approach has deep roots in various literatures but many observers still ask how PDIA-type reforms could work to foster successful reform in complex hierarchical developing country governments and whether these approaches really help foster reforms that better fit such complex contexts. This paper responds to such question by describing an action research study where PDIA is being used to retell a story of reform that has to date been limited. The action research study is in Mozambique's judicial sector and will examine whether and how a problem-driven iterative approach can (i) flush out the contextual factors that often limit reform success, (ii) provide a viable route to find and fit reforms that actually foster greater functionality, and (iii) promote the authority needed to ensure change is implemented and institutionalized.
Keywords: H11; O19; O55; 330; development; governance; reform